Ultrarapid spectroscopic gas detection via frequency-agile and compressed sensing - Yuan, Ziyue; Lou, Xiutao; Chu, Qi; Li, Tianfu; Dong, Yongkang (Applied physics. B, Lasers and optics, 2022)
In this work, taking the measurement of the absorption spectrum of acetylene gas at 6534.36 cm −1 as an example, an ultrarapid spectroscopic gas detection method based on frequency-agile and compressed sensing has been proposed and experimentally demonstrated. The frequency-agile technique is used to quickly and randomly scan the frequency of the probe light for obtaining stochastically sampled transmission spectrum data. The compressed sensing process includes the principal component analysis algorithm which obtains the sparse representation of the transmission spectrum, and the orthogonal matching-pursuit algorithm for reconstructing the transmission spectrum. The experimental results show a high degree of consistency between the original and the reconstructed transmission spectra (correlation coefficient > 0.99). With fewer sampling data, the gas sensing speed is increased by 13 times with 93% reduction in spectral data achieved.